In Situ Cytokine Expression and Morphometric Evaluation of Total Collagen and Collagens Type I and Type III in Keloid Scars - Isabela Rios da Silva; Luciana Colombo Rodrigues da Cunha Tiveron; Marcos Vinicius da Silva; Alberto Borges Peixoto; Carla Aparecida Xavier Carneiro; M. A. dos Reis; Pedro Carvalho Furtado; Bárbara Rocha Rodrigues; Virmondes Rodrigues; Denise Bertulucci Rocha Rodrigues (Mediators of Inflammation)
Keloids are characterized by excessive collagen deposition and growth beyond the edges of the initial injury, and cytokines may be related to their formation. The objective of this study was to evaluate the collagen fibers, analyze in situ expression of cytokines in keloid lesions, and compare to the control group. Results showed that there was a predominance of women and nonwhite and direct black ancestry. Keloid showed a significant increase in total and type III collagen. Significantly, the expression of mRNA for TGF-β in keloid was increased, the expressions of IFN-γ, IFN-γR1, and IL-10 were lower, and IFN-γR1 and TNF-α had no statistical difference. Correlations between collagen type III and TGF-β mRNA expression were positive and significant, IFN-γ, IFN-γR1, and IL-10 were negative and significant, and TNF-α showed no statistical difference. We conclude that there was a significant increase of total collagen in keloid and predominance of collagen type III compared to the controls, showing keloid as an immature lesion. There is a significant increase in TGF-β mRNA in keloid lesions, and a significant decrease in IFN-γ and IL-10, suggesting that these cytokines are related to keloid lesions.